Development of poly(urethane-ester)amide from corn oil and their anticorrosive studies. Issue 4 (19th May 2017) - Alam, Manawwer; Alandis, Naser M.; Ahmad, Naushad
ABSTRACT: Corn oil-based poly(urethane-ester)amide was synthesized from corn oil-based fatty amide diol, camphoric acid, and tolylene 2, 4-diisocyanate. The structure of corn polyesteramide and corn poly(urethane-ester)amide (CPEA) was confirmed by Fourier transform infrared, 1 H NMR, and 13 C NMR spectroscopic techniques. CPUEA coatings were made on mild steel strips and their physicomechanical analysis (scratch hardness, impact test, conical mandrel test, and pencil hardness tests) was performed by standard methods. The surface morphology of coatings was observed by scanning electron microscopy and thermal stability was assessed by thermogravimetric analysis/differential scanning calorimetry. Anticorrosion properties of CPUEA were observed in acidic, saline, and tap water medium at room temperature using potentiodynamic polarization technique. The results of CPUEA coatings exhibit good physicomechanical and anticorrosive properties and can find application up to 175°C.